OXIDATIVE STABILITY OF CANOLA OIL BY PHYSICO-CHEMICAL ANALYSIS AND FT-IR SPECTROSCOPY - Naz, Saima; Saeed, Rehana (Asian Journal of Pharmaceutical Research and Development, 2018)
This study was conducted to investigate the stability of canola oil after convention heating and repeated frying with potato piece. The progress of lipid oxidation was assessed in terms of physicochemical properties like viscosity, density, saponification value, peroxide value and acid value. Percentage free fatty acids (FFA) and percentage of glycerol present in each type of triglycerides was also calculated. Oxidative stability of the oil was studied by Fourier Transform-Infrared (FT-IR) spectroscopy. Results revealed that proportions of fatty acid changes with heating and frying, in result changes were observed in the intensities of spectral bands. Formation of secondary oxidation products were showed by the peak at frequency range 3753.48-3750 cm-1. Degree of chain length and degree of branching of fatty acids were calculated by FT-IR data. Keywords: canola oil, physicochemical characteristics, convention heating-frying, carbohydrate, FT-IR analysis